IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DALAM MENINGKATKAN KESELAMATAN MASYARAKAT (Kajian Terhadap Kasus Kecelakaan Lalu Lintas Di Kepolisian Resor Boyolali) - JATMIKO, DWI (Dinamika Hukum, 2015)
The purpose of this study is to examine and explain the implementation of Law No. 22 of 2009 on Traffic and Transportation in improving public safety in Police Boyolali. And assess and explain the constraints experienced by law enforcement to improve public safety and law-abiding realize according to Law No. 22 of 2009 on Traffic and Transportation. Road safety issues are closely related to traffic due to various accidents that cause harm and even death often occurs related traffic and use as ingredients. Therefore, preventive measures to safeguard the security and keselamantan on the road should be a priority that takes precedence. Law No. 22 of 2009 on Traffic and Transportation mandates that the role and function of the field of traffic police is So Public Education. Results of research and discussion that effort in order to realize a road safety is a shared responsibility between road users and the state apparatus competent to good road handling that is responsible for the procurement and maintenance of infra and suprastructures, facilities and road infrastructure as well as the setting and enforcement of the law it aims to be maintained as well as the preservation of the situation Kamseltibcar Then on the highway in a focused and achieve the expected goals, the active participation of the users of the road to ethics. Manners and compliance with laws and regulations in force is a most important thing in order to realize the security, safety, order and smooth traffic, according to modern policing system puts the community as a subject in maintaining personal safety will impact on the safety and regularity for pengguana other way. Constraints experienced by law enforcement to improve public safety and law-abiding realize according to Law No. 22 of 2009 on Road Traffic and Road Transport: a) Internal quality traffic police resources that have not been fully able to provide exemplary road users, treatment against violators of traffic officers. B) External factors, infrastructure road and have not yet reflect the aspect of safety, public transport management both central and local levels still reflect an unhealthy management, traffic arrangement disorder Keywords: Implementation, Safety, Society